MENGEMBANGKAN POTENSI DESA REJOYOSO MELALUI BUDIDAYA MAGGOT SEBAGAI UPAYA PEMANFAATAN SAMPAH ORGANIK - Yulia Eka Yanti; Tety Nur Cholifah; Hendra Rustantono; Hamidi Rasyid; Fahmanisatul Rodiyah; Muhammad Abdul Aziz (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2024)
Rejoyoso Village has the potential to utilize organic waste from leftover household activities. However, the people of Rejoyoso Village are less motivated to develop skills regarding organic waste processing. This is because people have no interest in or understanding of waste management. The aim of the KKN-T 16 UNIRA Rejoyoso Village activity program in 2024 is to utilize household organic waste effectively and innovatively and improve residents' skills in waste management. This KKN-T activity was carried out for 40 days with 16 participants in Rejoyoso Village, Bantur District. The activity stages are observation and identification of potential problems, processing observation data, program planning, implementation, which includes Focus Group Discussion (FGD), carrying out location permits, preparing tools and materials, carrying out socialization, and training on organic waste management through maggot cultivation. The final stage is monitoring and evaluating the results of the activities. The conclusion of this activity is that by empowering the community, people can broaden their knowledge and develop their skills through cultivating maggots in Rejoyoso Village, Bantur District, as an alternative use of organic waste.